Pengaruh Model Pembelajaran Number Head Together Terhadap Kemampuan Memberi Tanggapan dengan Santun Siswa Kelas IX SMP Negeri 03 Payaraman - Triliyani, Neza Seftanika; Agustina, Juaidah; Masnunah, Masnunah (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study is to determine whether the NHT (Number Head Together) learning model is effective in the ability to respond politely to class IX students of SMP Negeri 03 Payaraman. In this study, the research method used was the experimental method and sampling in this study used Simple Random Sampling because the sampling of sample members from the population was carried out randomly without considering the existing strata. Data collection techniques used pretest, posttest and interviews. Based on the results of the research and discussion on the influence of the number head together (NHT) learning model on the ability to respond politely to class IX students of SMP Negeri 03 Payaraman, Ogan Ilir Regency, it shows that the results of the two classes have a difference in the average value of the final experimental class of 85.79 which is greater than the average value of the final control class of 69.27, meaning that there is an influence of the number head together (NHT) learning model on the ability to respond politely to class IX students of SMP Negeri 03 Payaraman, Ogan Ilir Regency. The hypothesis shows that there is an influence of the number head together (NHT) learning model on the ability to respond politely to class IX students of SMP Negeri 03 Payaraman, Ogan Ilir Regency. This can be seen from the hypothesis test obtained by calculating = 5.352 where the calculation is greater than the table = 1.680. So, Ha can be accepted and Ho is rejected. Thus, Ha can be accepted, meaning that there is an influence of the number head together (NHT) learning model on the ability to respond politely to grade IX students of SMP Nelgelri 03 Payaraman, Ogan Ilir Regency.